Current Trends in Breast Reconstruction following Bilateral Prophylactic Mastectomy. Issue 4 (18th April 2022) - Hu, Vivian J.; McCleary, Sean P.; Smullin, Carolyn P.; Rosales Morales, Ricardo; Da Lio, Andrew L.
Abstract : Background: Individuals with genetic susceptibility to breast cancer may pursue bilateral prophylactic mastectomy (BPM) and subsequent breast reconstruction. This study aimed to characterize immediate reconstructive trends following BPM. Methods: The ACS-NSQIP database (2010 -2019) was used to examine differences in demographics and operative outcomes based on breast reconstruction technique following BPM and factors predicting reconstruction type. Results: Of 1945 patients (mean age, 43.8 ± 11.3 years), implant-based reconstruction (IBR) was most frequently (71.8%) performed following BPM. Patients who underwent IBR (n = 1396) were younger (42.6 years, P < 0.001), more likely to be White ( P < 0.05), and more likely to have a BMI less than 25 ( P < 0.001). Patients who underwent autologous reconstruction (AR) (n = 186, 45.8 years) were more likely to be Black or African American and have a BMI of 25–30. Patients who underwent mastectomy only (MO) without immediate reconstruction (n = 363) were older (47.6 years), more likely to be Asian, and more likely to have a BMI greater than 35. The MO cohort had the highest frequency of diabetes or smoking history. AR was associated with longer operations, longer lengths of stay, and increased complications. Increasing age and BMI were predictive of AR or MO compared to IBR. Smoking was predictive of MO. Conclusion: This is the first large-scale study of genetically susceptible patients who underwent BPM demonstrating a significant relationship between patient demographics, operative outcomes, and immediate reconstruction technique. These results provide valuable insight for surgeons and patients during the shared decision-making process.